PELAKSANAAN JAMINAN SOSIAL KEPADA DRIVER GOJEK DALAM HUBUNGAN KEMITRAAN - OKKY ADITYA PUTRA; Rahmawati Kusuma (Private Law, 2023)
This research examines the implementation and obstacles of social security provision for Gojek drivers in a partnership relationship, aiming to understand the implementation and barriers in carrying out social security. The study utilizes empirical legal research and descriptive qualitative analysis. Findings reveal that Gojek facilitates the Employment Social Security Agency (BPJS Ketenagakerjaan) registration, and drivers receive Health insurance from BPJS, Jasa Raharja Insurance, and the Reimbursement program. Various social guarantees obtained by Gojek Drivers are regulated in Minister of Transportation Regulation Number 12 of 2019, Minister of Labour Regulation Number 1 of 2016, Government Regulation Numbers 44 and 46 of 2015, Law Number 24 of 2011, Law Number 34 of 1964, and other related regulations. Driver awareness, lack of guidance and outreach, information and administrative constraints, as well as financial conditions and demographics (number of available drivers and/or number of service users), are identified as obstacles to the implementation of social security, especially in the city of Mataram